BIODIVERSITY MAPPING AND UTILIZATION OF MEDICINAL PLANTS AS DEVELOPMENT DESA TABIB CONCEPT IN TAMANSARI VILLAGE, INDONESIA - Septianingrum, Shinta Tri Ananda Putri; Ramadhan, Syahrul; Devi, Sarda Ika; Sukamto, Asroful Waro'faid; Hotijah, Husnul; Intan, Presti Dewi; Absor, Farhad Ulil; Ramadhania, Farhaiza; Sakinah, Salsabila Amalia; Saptiansyah, Refaldi; Zulfikar, Mochamad; Sagita, Ahmad Danang; Hakim, Rahmat; Fikriansyah, Mohammad; Asdiyanta, Amin Nur; Puspaningtyas, Azizah; Akbari, Gilang Avrilio; Fandi, Ryo Al; Prayogi, M. Fahmi Dimas; Santosa, Gusti Ayu Illiyin Putri; Andris, Achmad Julian; Muhammad, Anta Dzaky; Sebayang, Susy Katikana (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2025)
Medicinal plants in Tamansari Village are starting to be forgotten by the people while their potential is very abundant. The people of Tamansari Village are also not familiar with the medicinal plants around them and how to use these plants. Therefore, it is necessary to empower the community to optimize the potential of medicinal plants in Tamansari Village. This is also done so that Tamansari Village is not only known as a tourist village but also a healer village. Therefore, several empowerment sub-activities were carried out, including the formation of conservation groups, mapping of medicinal plant biodiversity, cultivation, product processing, and marketing. From these activities, Tamansari Village can now develop the concept of a healer's village with the community knowing medicinal plants and having the ability to utilize their potential.